2017
DOI: 10.1016/j.cgh.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sleeve Gastroplasty Significantly Reduces Body Mass Index and Metabolic Complications in Obese Patients

Abstract: ESG is a minimally invasive and effective endoscopic weight loss intervention. In addition to sustained total body weight loss up to 24 months, ESG reduced markers of hypertension, diabetes, and hypertriglyceridemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
149
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(170 citation statements)
references
References 39 publications
13
149
0
3
Order By: Relevance
“…In the largest multicenter retrospective study conducted to date (n = 248), TBWL with ESG was reported to be 15.2% at 6 months . These results are similar to prior smaller‐scale prospective studies . Long‐term effectiveness of ESG was confirmed at 24 months with a TBWL of 18.6% …”
Section: Gastric Remodeling Proceduressupporting
confidence: 81%
See 3 more Smart Citations
“…In the largest multicenter retrospective study conducted to date (n = 248), TBWL with ESG was reported to be 15.2% at 6 months . These results are similar to prior smaller‐scale prospective studies . Long‐term effectiveness of ESG was confirmed at 24 months with a TBWL of 18.6% …”
Section: Gastric Remodeling Proceduressupporting
confidence: 81%
“…Unlike POSE, ESG does not include suturing the fundus because it is quite difficult to perform in the retroflexed position with this device. Since the first technical feasibility study conducted on four patients by Abu Dayyeh et al was published, many subsequent studies have demonstrated the safety and efficacy of ESG in both weight loss and improvement in metabolic and physiologic parameters in patients with BMI between 30.0 and 40.0 kg/m 2 . In the largest multicenter retrospective study conducted to date (n = 248), TBWL with ESG was reported to be 15.2% at 6 months .…”
Section: Gastric Remodeling Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…45,52 In addition to sustained total bodyweight loss, endoscopic sleeve gastroplasty has been associated with a reduction in hypertension, diabetes and hypertriglyceridemia markers. 45,52 The EndoBarrier is a duodenal bypass sleeve anchored to the duodenal bulb through a nitinol crown with barbs. The sleeve is advanced into the small bowel, allowing undigested food to reach the jejunum and creating a physical barrier between the food and the intestinal wall.…”
Section: Bariatric Endoscopic Surgerymentioning
confidence: 99%